Development of autotaxin inhibitors: A series of zinc binding triazoles. Issue 13 (15th July 2018) - Thomson, Christopher G.; Le Grand, Darren; Dowling, Mark; Brocklehurst, Cara E.; Chinn, Colin; Elphick, Lucy; Faller, Michael; Freeman, Mark; Furminger, Vikki; Gasser, Cornelia; Hamadi, Ahmed; Hardaker, Elizabeth; et al.
Graphical abstract: Highlights: PF-8380 has been used as a template to design a new series of ATX inhibitors. Reduction of crystallinity was key to improving solubility of the new series. Selectivity and good oral exposure was achieved with this series. Compound 12 shows a direct PK-PD relationship with inhibition of production of LPA. Abstract: A series of inhibitors of Autotaxin (ATX) has been developed using the binding mode of known inhibitor, PF-8380, as a template. Replacement of the benzoxazolone with a triazole zinc-binding motif reduced crystallinity and improved solubility relative to PF-8380. Modification of the linker region removed hERG activity and led to compound 12 – a selective, high affinity, orally-bioavailable inhibitor of ATX. Compound 12 concentration-dependently inhibits autotaxin and formation of LPA in vivo, as shown in pharmacokinetic-pharmacodynamic experiments.